Dynamics of Crowded Vesicles: Local and Global Responses to Membrane Composition. - Daniel A Holdbrook; Roland G Huber; Thomas J Piggot; Peter J Bond; Syma Khalid (PLoS ONE)
The bacterial cell envelope is composed of a mixture of different lipids and proteins, making it an inherently complex organelle. The interactions between integral membrane proteins and lipids are crucial for their respective spatial localization within bacterial cells. We have employed microsecond timescale coarse-grained molecular dynamics simulations of vesicles of varying sizes and with a range of protein and lipid compositions, and used novel approaches to measure both local and global system dynamics, the latter based on spherical harmonics analysis. Our results suggest that both hydrophobic mismatch, enhanced by embedded membrane proteins, and curvature based sorting, due to different modes of undulation, may drive assembly in vesicular systems. Interestingly, the modes of undulation of the vesicles were found to be altered by the specific protein and lipid composition of the vesicle. Strikingly, lipid dynamics were shown to be coupled to proteins up to 6 nm from their surface, a substantially larger distance than has previously been observed, resulting in multi-layered annular rings enriched with particular types of phospholipid. Such large protein-lipid complexes may provide a mechanism for long-range communication. Given the complexity of bacterial membranes, our results suggest that subtle changes in lipid composition may have major implications for lipid and protein sorting under a curvature-based membrane-sorting model.